2019
DOI: 10.1038/s41561-019-0414-7
|View full text |Cite
|
Sign up to set email alerts
|

Selenium isotopes as tracers of a late volatile contribution to Earth from the outer Solar System

Abstract: The origin of Earth’s volatiles has been attributed to a late addition of meteoritic material after core-mantle differentiation. The nature and consequences of this 'late veneer' are debated, but may be traced by isotopes of the highly siderophile, or iron-loving, and volatile element selenium. Here we present high-precision selenium isotope data for mantle peridotites, from double spike and hydride generation multi-collector inductively coupled plasma mass spectrometry. These data indicate that the selenium i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
44
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 44 publications
(135 reference statements)
7
44
0
Order By: Relevance
“…However, the first sets of observations of K isotopes in meteorites, CAI, chondrules and in the Moon revealed a rather different pattern with little or no fractionation with increasing K depletion 24 . More recent work has shown that, except for CAI 25 , the magnitude of isotope fractionations reported in planetary materials are smaller than expected for a purely kinetic Rayleigh-type loss process (Rb, Zn, K, Mg, Si, Fe, Cu and Se) 15,[26][27][28][29][30][31][32][33][34][35] . Thus, at all scales of planetary accretion, some processes acted to limit the large kinetic isotope fractionation expected for evaporation or condensation.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…However, the first sets of observations of K isotopes in meteorites, CAI, chondrules and in the Moon revealed a rather different pattern with little or no fractionation with increasing K depletion 24 . More recent work has shown that, except for CAI 25 , the magnitude of isotope fractionations reported in planetary materials are smaller than expected for a purely kinetic Rayleigh-type loss process (Rb, Zn, K, Mg, Si, Fe, Cu and Se) 15,[26][27][28][29][30][31][32][33][34][35] . Thus, at all scales of planetary accretion, some processes acted to limit the large kinetic isotope fractionation expected for evaporation or condensation.…”
Section: Introductionmentioning
confidence: 88%
“…(0, ) = ,0 > 0 (27) If the species of interest is in trace amount then the diffusion coefficient can be considered to be independent of the concentration. Under these conditions, the partial differential equation can be solved analytically to yield 81 the time-dependent solution of equation 24can be written as…”
Section: Influence Of Local Partial Pressurementioning
confidence: 99%
“…Mass-independent ruthenium isotopic variations among meteorites and the Earth have provided evidence that the late veneer was derived from reduced and volatile-poor inner solar system materials most similar to enstatite chondrites 5 , 11 , 12 , 19 . This is in contrast to constraints from relative abundances of volatile elements such as selenium (Se) – tellurium (Te) – sulphur (S) and the Se isotope composition in the silicate Earth that were used to argue for a CM or CI carbonaceous chondrite-like late veneer composition 2 , 9 , 10 . Owing to its distinct Ru isotope composition, volatile-rich carbonaceous chondrite-like material from the outer solar system was excluded as possible late veneer source material 5 , 11 and thus, the late veneer appeared unlikely to be the primary source of water and volatiles on Earth 5 , 11 .…”
mentioning
confidence: 97%
“…However, the timing of this accretion remains controversial 5 8 . It was proposed that volatile elements were added to Earth by late accretion of a late veneer consisting of carbonaceous chondrite-like material after core formation had ceased 6 , 9 , 10 . This view, however, could not be reconciled with the distinct ruthenium (Ru) isotope composition of carbonaceous chondrites 5 , 11 compared to the modern mantle 12 , and in fact also not with any known meteorite group 5 .…”
mentioning
confidence: 99%
See 1 more Smart Citation